Effect of distribution and concentration of topically applied neonicotinoid insecticides in buffalograss, Buchloe dactyloides, leaf tissues on the differential mortality of Blissus occiduus under field conditions. Issue 2 (30th August 2012) - Stamm, Mitchell D; Heng‐Moss, Tiffany M; Baxendale, Frederick P; Siegfried, Blair D; Gaussoin, Roch E; Snow, Daniel D; Cassada, David A
Abstract BACKGROUND: Neonicotinoid insecticides are generally efficacious against many turfgrass pests, including several important phloem‐feeding insects. However, inconsistencies in control of western chinch bugs, Blissus occiduus, have been documented in field efficacy studies. This research investigated the efficacy of three neonicotinoid insecticides (clothianidin, imidacloprid and thiamethoxam) against B. occiduus in buffalograss under field conditions and detected statistically significant differences in B. occiduus numbers among treatments. A subsequent study documented the relative quantity and degradation rate of these insecticides in buffalograss systemic leaf tissues, using HPLC. RESULTS: Neonicotinoid insecticides initially provided significant reductions in B. occiduus numbers, but mortality diminished over the course of the field studies. Furthermore, while all three neonicotinoids were present in the assayed buffalograss leaf tissues, imidacloprid concentrations were significantly higher than those of clothianidin and thiamethoxam. Over the course of the 28 day study, thiamethoxam concentrations declined 700‐fold, whereas imidacloprid and clothianidin declined only 70‐fold and 60‐fold respectively. CONCLUSIONS: Field studies continued to verify inconsistencies in B. occiduus control with neonicotinoid insecticides. This is the first study to document the relative concentrations of topically applied neonicotinoid insecticides in buffalograss systemic leaf tissues. Copyright © 2012 Society of Chemical Industry